Pelatihan pembuatan video profil sekolah di SMA se-kabupaten Lombok Timur - Kholida Ismatulloh; Jamaluddin Jamaluddin; Yosi Nur Kholisho; Baiq Desi Dwi Arianti; Rasyid Hardi Wirasasmita; Muhammad Zamroni Uska; Samsul Lutfi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The rapid development of science and technology, along with the advent of the Fourth Industrial Revolution and Society 5.0, has significantly impacted all aspects of life, including education. In response to these developments, the Ministry of Education and Culture has strengthened the teaching of informatics in the latest curriculum, "Independent Learning." However, many schools are not adequately prepared to handle informatics subjects due to a lack of competent teachers. Therefore, the educational informatics program has the opportunity to engage in community engagement by providing training and assistance related to informatics subjects to students in vocational high schools (SMK). This engagement involves the participation of educational informatics lecturers and several students. The program consists of 3 to 4 sessions with students from grade XII at SMK Qurrota A’yun Joben. The training covers fundamental networking, resource sharing, connectivity, and communication aspects, followed by the creation of school profile videos. Participants are instructed in techniques for capturing footage, video editing, and multimedia design using various applications. The posttest results reveal a significant improvement in participants' skills in graphic design (85%), scenario creation (93%), video capturing techniques (86%), and video editing (96%). This engagement offers SMK Qurrota A’yun the opportunity to promote their school through captivating profile videos, thus enhancing the interest of potential students' parents and facing competition in the age of social media. The training and assistance in school profile video creation effectively enhance participants' multimedia management skills and facilitate school promotion in a more compelling manner. Video profiling proves to be an efficient and effective medium for conveying information and promotions, especially in the current era of social media. Leveraging multimedia technology has become essential in fostering school competitiveness and harnessing the full potential of the community in the Society 5.0 era.